English in Public Schools Located in Metropolitan Lima, Peru: An Exploratory Analysis of Fifth-Year Secondary School Students’ Level and Perceptions - Morales Huaman, Andrea Isabel (2018)
English Language Teaching (ELT) public policies are present in most of the countries of the Americas due to the importance of said language in the international context. The objective of this research was to know the English level of fifth-year secondary school students in public schools located in Metropolitan Lima, Peru, as well as their perceptions of their own English learning process within the framework of the new national plan called Inglés, Puertas al Mundo (English, Doors to the World). The sample was composed of 72 students from four schools of the city. This study was conducted using an exploratory design which had both quantitative and qualitative components. The instruments used were a standardized English test (New Inside Out Quick Placement Test) and a structured interview guide. The results revealed that the students’ English level in grammar and vocabulary is below the level outlined in the national policy. Regarding the perception of their own learning, students have different motivations to learn English, and enjoy the blended model introduced by the national English plan. However, they agree that their English level is very basic and that they would not be able to reach the established communication objectives after graduating from high school.